Education and Health Status of Child Workers of Dhaka City - Khan, Madiha (Global Disclosure of Economics and Business, 2014)
Children are the future of the country. Every child has the right to grow up in the right way. But it is a matter of great regret that child labor is highly prevalent in this country, and all child workers are deprived of their rights. Child workers are engaged in various types of works in Bangladesh. Many of the jobs that children perform in this country are considered hazardous and put their physical and mental development at risk. Child labor is work that deprives children of a childhood and affects their health and education. So, the government should take effective steps to withdraw children from hazardous jobs and offer incentives to attend school and improve law enforcement to eliminate child labor.JEL Classification Code: J13; I18; K32